Conflict Management in Maintaining Organizational Sustainability - Rofikatul Maula (Journal of Research in Educational Management, 2022)
Conflict management is an important aspect in maintaining organizational sustainability. Conflicts can arise from a variety of sources, such as differences of opinion, goals or incompatible interests. However, when managed properly, conflict can be a source of innovation and improvement in organizations. This study aims to explore how conflict management can be used to maintain organizational sustainability. The research method used is a qualitative case study type. The results of this study indicate that leaders carry out: effective communication, tolerance, motivation and giving appreciation to maintain organizational sustainability at Nurul Jadid Paiton High School Probolinggo.